Ensuring Equality of Labour Rights of Workers with Family Responsibilities in Russia and Kazakhstan: Problems of Implementation of International Labour Norms - Davletgildeyev Р.Ш.; Zarubin Д.В. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article is devoted to the study of the problem of implementation in the Russian Federation and in the Republic of Kazakhstan of international labour norms aimed at ensuring equality of labour rights of workers (men and women) with family responsibilities, raising young children (under the age of three years). It is noted that the main international treaty in the designated area, according to which Russia and Kazakhstan bear international legal obligations, is the International Labour Organization Convention No. 156 “On Equal Treatment and Equal Opportunities for Working Men and Women: Workers with Family Responsibilities”. Within the framework of this convention, aspects related to ensuring the legal equality of parents (fathers and mothers) raising children under the age of three years are considered, when they are involved in night work, overtime work, work on weekends and non-working holidays and when they are sent to official business trips, as well as issues related to the establishment of employees (men and women) with young children, labour guarantees, providing them with equal protection against dismissals at the initiative of the employer. In addition, in relation to the Russian Federation, within the framework of the provisions of the European Social Charter and the European Convention on Human Rights (based on the decisions of the European Court of Human Rights), an aspect related to the restriction of the right of men to be granted parental leave is being considered. In conclusion, attention is drawn to the need to make appropriate changes to the labour legislation of Russia and Kazakhstan.